2020
DOI: 10.1155/2020/5309814
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and Chaos of a Discrete Predator-Prey Model with Crowley–Martin Functional Response Incorporating Proportional Prey Refuge

Abstract: The paper investigates the dynamical behaviors of a two-species discrete predator-prey system with Crowley–Martin functional response incorporating prey refuge proportional to prey density. The existence of equilibrium points, stability of three fixed points, period-doubling bifurcation, Neimark–Sacker bifurcation, Marottos chaos, and Control Chaos are analyzed for the discrete-time domain. The time graphs, phase portraits, and bifurcation diagrams are obtained for different parameters of the model. Numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Ghosh et al [14] studied the effects of extra food for predator with prey refuge. Santra et al [15] investigated the dynamical actions with Crowley-Martin functional response-associated prey refuge. Finally, Molla et al [16] suggested a model for Holling type-II prey-predator interactions in a prey refuge.…”
Section: Jaber and Bahloolmentioning
confidence: 99%
“…Ghosh et al [14] studied the effects of extra food for predator with prey refuge. Santra et al [15] investigated the dynamical actions with Crowley-Martin functional response-associated prey refuge. Finally, Molla et al [16] suggested a model for Holling type-II prey-predator interactions in a prey refuge.…”
Section: Jaber and Bahloolmentioning
confidence: 99%
“…where the functions f 1 and g 1 denote the terms in model (9) in variables (x n , y n ) with the order at least two.…”
Section: Neimark-sacker Bifurcationmentioning
confidence: 99%
“…Nature offers some amount of protection to some prey populations in the form of refuge dimensions. In some instances, refugia give a prolonged prey-predator interaction [8,9] to reduce the probability of extinction due to predation activity. is phenomenon has been investigated extensively by many researchers in the discrete domain of refuse concepts [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interplay between the species may lead to dynamics of stunning complexity. There is a vast literature regarding such models and models which also include age or stage structure, see [15][16][17][18][19][20][21][22][23][24][25], and more recently, cf [26][27][28][29] and references therein, the question of how to control and stabilize chaotic behaviour in prey-predator systems has been addressed. The dynamics found in such systems strongly depends on compensatory or overcompensatory recruitment.…”
Section: Introductionmentioning
confidence: 99%